Analisis Kebijakan Akuntansi Keuangan dalam Penetapan Sisa Lebih Pembiayaan Anggaran (SILPA) pada APBD Kabupaten Lombok Timur Tahun Anggaran 2024 - Lili Andriani; Nova Hari Santhi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
Local government accounting policies provide the foundation for financial reporting. The Budget Realization Report (LRA) compares budgeted and actual figures, with the resulting balance recorded as the Sisa Lebih Pembiayaan Anggaran (SILPA, excess financing surplus). This study in East Lombok Regency aims to quantify the SILPA in the 2024 APBD and to analyze the financial accounting policies used in its determination. A descriptive approach combining qualitative and quantitative methods was applied. Data were collected via structured interviews with local finance officials, observations, and document analysis of APBD financial reports. Qualitative data were reduced and presented to describe policy factors, while quantitative analysis computed the SILPA value. Results show the 2024 LRA recorded a SILPA of IDR 6,414,658,153.17, indicating unused budget funds. These funds will finance the 2025 budget deficit for investment and equity in regional companies. The accounting policy for SILPA determination considered key principles such as prudence, substance over form, and materiality, in accordance with government accounting standards (e.g. applying the conservatism principle to avoid recognizing uncertain revenues). This analysis highlights how regional financial policies influence the management of budget surpluses.